Does intellectual capital of “capital” matter? Investigation of small business revenue - Siswanti Siswanti; Syamsul Ridjal; La Ode Sumail (Jurnal Inovasi Ekonomi, 2021)
The main purpose of this study is to examine the effect of length of business on revenue by mediating financial literacy and moderated by capital management ability. Financial literacy and capital management ability in this paper we call intellectual capital. This study used a saturated sample of 71 respondents. Data were analyzed using descriptive analysis and path analysis. The results of this study show that the length of business has a positive relationship to revenue. Furthermore, in general, knowledge-based intellectual capital has a statistically negative impact on revenue, but this finding is biased. Meanwhile, capital management which is an experience-based intellectual capital has a positive impact on revenue. Last but not least, the moderating variable of the place of business is proven to increase small business revenue.